2007
DOI: 10.1016/j.taap.2007.01.012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro atrazine-exposure inhibits human natural killer cell lytic granule release

Abstract: The herbicide atrazine is a known immunotoxicant and an inhibitor of human Natural Killer (NK) cell lytic function. The precise changes in NK cell lytic function following atrazine exposure have not been fully elucidated. The current study identifies the point at which atrazine exerts its affect on the stepwise process of human NK cell mediated lyses of the K562 target cell line. Using intracellular staining of human peripheral blood lymphocytes, it was determined that a 24 h in vitro exposure to atrazine did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…In summary, AZ-induced damaged testis observed in our study might result from the down regulation of these genes related to reproduction. Numerous studies have shown that AZ influences the immune system through decreasing cell-mediated and humoral immunity, inhibiting cytokine production, dendritic cell maturation and natural killer cell activity (Hooghe et al, 2000;Karrow et al, 2004;Pinchuk et al, 2007;Pruett et al, 2006;Rooney et al, 2003;Rowe et al, 2007Rowe et al, , 2008. We found that genes involved in the complement system such as c2, c3, cfh were decreased by AZ treatment.…”
Section: Gene Namementioning
confidence: 62%
“…In summary, AZ-induced damaged testis observed in our study might result from the down regulation of these genes related to reproduction. Numerous studies have shown that AZ influences the immune system through decreasing cell-mediated and humoral immunity, inhibiting cytokine production, dendritic cell maturation and natural killer cell activity (Hooghe et al, 2000;Karrow et al, 2004;Pinchuk et al, 2007;Pruett et al, 2006;Rooney et al, 2003;Rowe et al, 2007Rowe et al, , 2008. We found that genes involved in the complement system such as c2, c3, cfh were decreased by AZ treatment.…”
Section: Gene Namementioning
confidence: 62%
“…In vitro studies using human cells have found that micromolar doses of atrazine can decrease mitogen-induced cytokine production and proliferation by peripheral blood mononuclear cells [31]. Whalen et al [32] and our own laboratory [33] have demonstrated that in vitro atrazine exposure results in a dose-dependent decrease in natural killer cell lytic function. We have also demonstrated a dose-dependent decrease in the lytic activity of alloreactive murine T cells [33].…”
Section: Non-developmental Immunotoxic Effects Of Atrazinementioning
confidence: 96%
“…[32] and our own laboratory [33] have demonstrated that in vitro atrazine exposure results in a dose‐dependent decrease in natural killer cell lytic function. We have also demonstrated a dose‐dependent decrease in the lytic activity of alloreactive murine T cells [33]. Clearly, these results indicate that both in vivo and direct in vitro exposure to atrazine decreases immune function in human and murine lymphocytes.…”
Section: Non‐developmental Immunotoxic Effects Of Atrazinementioning
confidence: 99%
“…In vitro atrazine exposure is reported to affect various cell types in humans; for example, increase in cellular proliferation in human intestinal epithelial cells,[ 8 ] decrease in growth of normal human fibroblasts,[ 9 ] and disruptions in the cell cycle regulation of immortalized human liver cells. [ 10 ] It has also decreased the natural killer cell-specific activity in peripheral blood lymphocytes[ 11 ] and cell viability in Chinese Hamster Ovary Cells. [ 12 ] One of the mechanisms which could be related to these cellular effects of atrazine may be its actions on mitochondrial functions in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%